Seizing the moment : from early warning to early action (International Crisis Group Avenue Louise 149, 1050 Brussels, Belgium, 2016)
After a period of relative calm, an upsurge of crises is testing the international system, pitting major powers and regional players against one another and highlighting the weaknesses of preventive diplomacy. Governments and international organisations were taken by surprise by the Arab uprisings in 2011 and slow to react to crises in South Sudan and the Central African Republic (CAR) in the years that followed. Global and regional rivalries have weakened diplomacy over Syria, Ukraine and the South China Sea. Policymakers, stretched by the symptoms of this wave of instability, including mass displacement and the spread of transnational terrorism, struggle to focus on conflict prevention.
Keywords: Relaciones Internacionales; Derecho internacional; Terrorismo internacional; Guerra